STRATEGI DIGITAL MARKETING PADA UMKM DONUTS RAINBOW SEBAGAI PENUNJANG KEGIATAN PROMOSI - Ita Purnama; Hidratul Iftar; Nurirna Sakinah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economic growth of Indonesia. In the current era of technological advancement and digitalization across various sectors, MSMEs, as a type of business, have a significant impact on economic development and need to progress in the field of technology, particularly in marketing their products. The objective of this community service is to develop MSMEs in terms of digital marketing and expand their marketing networks. Donats Rainbow MSME is an example that requires assistance in digital marketing. The method used in this community service consists of four stages: survey, digital marketing socialization, digital marketing assistance, and maintenance and evaluation stages. The form of community service aims to develop and actively participate in digital marketing assistance for Donats Rainbow MSME to enable them to have an unrestricted marketing network beyond the local market.